Svák Ján, Mareček Lukáš et al.: Medzinárodné právo verejné a úvod do verejného medzinárodného práva [Public International Law and Introduction to Public International Law] - Petra Paľuchová (Bratislava Law Review)
In a rapidly changing world, international law often seems to recede into the background, overshadowed by domestic legal disciplines. Students tend to prioritise information that appears to have direct practical applicability, leading to a diminished focus on international law in favour of national legal frameworks. Given the overwhelming influx of information they encounter daily, it is perhaps natural for students to favour subjects they perceive as immediately relevant to practice, a relevance they do not always associate with international law. As a legal framework governing inter-state relations and international obligations, it may appear distant from the routine legal challenges they anticipate encountering in their professional careers. The understanding of peremptory norms, enforcement mechanisms, or the resolution of disputes between states may seem less pertinent, as their practice is unlikely to involve the regular handling of inter-state conflicts.